Symbols of Power and Roman Clothing in Oriental Divinities - Romero Mayorga, Claudina (Eikón / Imago, 2013)
From the first century AD certain deities outside the Greco-Roman pantheon underwent a transformation in their iconography: the muscle-heroic cuirass or the whole Roman military uniform was introduced in their usual representations. This study attempts to discern the possible causes of this phenomenon and to analyze the syncretic images in different areas, focusing on Egypt and Syria.